MUBASYAROH METHOD FOR MAHARATUL KALAM AT ISLAMIC BOARDING SCHOOL ISY KARIMA INDONESIA - Taufik Hidayat Stang; Nur Rochim Maksum; Hafidz Hafidz; Rahmat Hidayat Stang (Universitas Muhammadiyah Surakarta, 2024)
The success of a teacher in teaching is inseparable from the methods used to create quality output. One example is the mubasyaroh method, this method is used to teach Arabic in increasing maharatul kalam. This research was conducted to describe the teaching process of Maharatul Kalam by using the mubasyaroh method to find out the teaching results and the advantages and disadvantages. This study uses qualitative research using qualitative descriptive. This study uses two data sources, namely primary data and secondary data, taking data from informants involving students, teachers, and principals, with observation, interview, and documentation techniques. Based on the data obtained, it can be concluded that the teaching of Maharatul Kalam using the mubasyaroh method has been effective. In the process, students are required to communicate, listen, and record new vocabulary delivered by the teacher. Judging from the analysis of the data obtained in teaching maharatul kalam with the mubasyaroh method based on the level of effectiveness in teaching, it can be seen from the student scores which show that more than 83.4% of students have a score of ≥ 60 with an average score of 83 out of 18 students.